Nanoindentation of silicon implanted with hydrogen: effect of implantation dose on silicon's mechanical properties and nanoindentation-induced phase transformation. (14th July 2017) - Jelenković, Emil V; To, Suet; Goncharova, Lyudmila V; Wong, Sing Fai
Abstract: Implantation of hydrogen in single-crystal silicon (c-Si) is known to affect its machining. However, very little is reported on the material and mechanical properties of hydrogen-implanted silicon (Si). In this article, near-surface regions ( 0–500 nm) of lightly doped (1 0 0) Si were modified by varying the hydrogen concentration using ion implantation. The maximum hydrogen concentration was varied from 4 × 10 20 to 3.2 × 10 21 cm −3 . The implanted Si was investigated by nanoindentation. From the dynamic nanoindentation test, it was found that in hydrogen-implanted Si hardness is increased significantly, while the elastic modulus is reduced. The nanoindentation-induced Si phase transformation was studied under different load/unload rates and loads. Raman spectroscopy revealed that the hydrogen implantation tends to suppress Si-XII and Si-III phases and facilitates amorphous Si formation during the unloading stage of nanoindentation. Both the mechanical properties and phase transformations were qualitatively related not only to the hydrogen concentration, but also to the implantation-generated defects and strain.